The Effect of Operating Expenses, Business Income, Receivables Turnover, and Total Debt on Net Profit in Food and Beverage Companies - Tsalsa Dyna Shofwatin; Ernest Alang Wung (Fairness, 2025)
Objective: This study aims to empirically examine the effect of operating expenses, operating income, accounts receivable turnover, and total debt on net income in manufacturing companies listed on the Food & Beverage sub-sector of the Indonesia Stock Exchange for the period 2020–2024. Research Design & Methods: Using a descriptive quantitative approach, this study employs a panel data regression model that combines time series observations (2020–2024) and cross-sectional observations of 10 companies, then tests the best model from the panel regression. Findings: Based on the test results, the best model found was the FEM model. The analysis shows that business income and total debt have a positive and significant effect on net profit. Conversely, operating expenses and accounts receivable turnover were not found to have a statistically significant effect on profit margin. Implications & Recommendations: These results confirm that F&B companies need to prioritize revenue growth and prudent debt management, while maintaining cost efficiency and accounts receivable management. Further research is recommended to include variables such as company size, age, innovation, and macroeconomic factors, using a broader approach and analysis period. Contribution & Value Added: This study provides empirical evidence on the effect of operating expenses, operating income, accounts receivable turnover, and total debt on net income in Indonesia's F&B manufacturing sector and offers strategic insights for managers and investors in making more effective business decisions.